Ta. Rā. Su. baduku-bareha - Krṣṇarāya, Śā. Maṃ (Viśvabhārati Prakāśana, 1982)
Festschrift honoring Taḷakina Rāmasvāmayya Subbarāv, b. 1923, Kannada litterateur, on his 63rd birthday; comprises articles on his life and works.